Весняно-літні та літні календарні пісні. Частотна каталогізація текстів і наспівів - Ефремова, Л. (Народна творчість та етнографія, 2006)
This article is dedicated to the frequency aspect of the transitive and migrational forms of the spring and the summer ritual carols according to their text plots and melody types. Music and text analysis of the Ukrainian carols of the spring-summer cycle (from the catalogue of the Ukrainian singing folklore), based on the typology of its melodies helps to figure out regularities of the formation of the stylistic features, its genetic and hierarchy of its performance in the calendar cycle.